Psichologine parama sportininkams daugiamecio rengimo procese - Vysochina, N. (Sporto Mokslas-Sport Science, 2016)
The paper deals with the peculiarities and the tasks of psychological support for athletes in process of longterm perfection. Specificity and differences in psychological function manifestation (thinking, feelings, intuition, and sensations) at different stages of the long-term preparation as an indicator of athletes` psychological state have been studied. Psychological factors, influencing the process of the long-term perfection of athletes, have been analysed with account for the dynamics of rational and irrational psychological functions. Psychological support tasks at each stage of the long-term preparation have been formulated on the basis of expert survey results reflecting the level of psychological function development in athletes. Psychological support tasks being actual at all stages of the longterm preparation of athletes have been singled out as well. The features of psychological support for the athletes at the stage of withdrawal from elite sport, being the least studied in sports psychology, have been considered separately. The system of knowledge about psychological support for the long-term preparation of athletes including four major blocks of its realization has been formed: psychological preparation, organizational and methodical aspects, psychological components of providing the efficiency of athletic preparation, and the directions of psychological support in the process of selection and orientation of athletes` preparation.